The Effect of Banking Organisational Culture on Employee Retention in Karnali Province of Nepal (Quest Journal of Management and Social Sciences, 2025)
Background: Employee retention is a critical organisational capability that enables institutions to sustain their workforce and minimise turnover. Central to this concept is creating strategies that cultivate a supportive, engaging environment where employees feel valued and motivated to remain with the organisation. In sectors like banking, which are marked by high dynamism and competitive pressures, Retention is integral to maintaining operational stability and achieving long-term success. Purpose: This research investigates the impact of organisational culture on employee retention within Karnali Province's banking sector. It evaluates four cultural dimensions: reward and recognition, workplace environment, effective communication, and coworkers' behaviour to determine their role in influencing retention rates and identify strategies for mitigating turnover challenges. Methods: The study employed a positive research paradigm and a causal-comparative design to explore relationships between organisational culture and employee retention. Data were collected using a structured questionnaire distributed to 325 banking sector employees in Karnali Province. Statistical analysis, conducted via SPSS software, applied quantitative exploratory techniques to evaluate correlations between retention outcomes and four cultural variables.Findings: The analysis identified statistically significant positive relationships between employee retention and three cultural factors: reward and recognition systems, workplace environment, and effective communication practices. In contrast, coworkers' behaviour demonstrated a negligible impact on retention decisions. Conclusion: Organisational culture is pivotal to retention strategies in Karnali's banking sector. Institutions should prioritise institutional structured recognition programs, optimising workplace environments, and enhancing transparent communication channels to reduce turnover. While coworker dynamics showed limited influence, reinforcing the other cultural pillars can foster employee loyalty and organisational resilience, positioning banks for sustained growth and competitiveness.Keywords: Reward and recognition, Workplace environment, Effective communication, Coworkers' behaviour, and Employee RetentionJEL Codes: J28, J63, M12, M14, G21